Pengaruh Budaya Perusahaan Terhadap Sistem Manajemen Mutu ISO 9001:2015 Klausul 8, Klausul 9 dan Klausul 10 untuk Meningkatkan Kualitas Produk (Studi Kasus: Perusahaan Manufaktur) - Muchamad Nurdin Alwi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
Producing quality products is an important requirement that must be met by the organization to achieve customer satisfaction, so a new vision is needed about how the role of corporate culture is to implement corporate quality management. PT N is one of the manufacturing companies that produces metalsubstrate in Indonesia. In its application, there are problems in the company in terms of quality within the company so that it requires an analysis of what factors influence the influence of industrial culture on some clauses the ISO 9001: 2015 Quality Management System, namely clause 8 on operations, clause 9 on performance evaluation and clause 10 on improvement to improve product quality. Data analysis in this study involved all employees totaling 97 respondents of company employees with data analysis techniques using PLS-SEM. The results of this study obtained that corporate culture has a significant effect on operations, performance evaluation and improvement, operations and performance evaluation have a positive but insignificant effect on product quality and improvement has a positive and significant effect on product quality